2016
DOI: 10.1016/j.joca.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Prospective change in daily walking over 2 years in older adults with or at risk of knee osteoarthritis: the MOST study

Abstract: Objective Radiographic disease and knee pain are thought to decrease physical activity in people with knee osteoarthritis (OA), but this has not been formally studied. We examined change in objectively measured daily walking over two years and evaluated the association of certain risk factors with reduced walking among adults with or at risk of knee OA. Design Steps/day over 7 days were collected at baseline and two years later in subjects with or at risk of knee OA from the Multicenter Osteoarthritis Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 50 publications
0
21
0
1
Order By: Relevance
“…White et al 44 found that people with underlying structural worsening trended towards less walking and were more likely to fall below the 6000 step/day threshold, suggesting functional limitation. People who are predisposed to OA or have confirmed OA should not be discouraged from walking and can benefit from AA 45 .…”
Section: Discussionmentioning
confidence: 99%
“…White et al 44 found that people with underlying structural worsening trended towards less walking and were more likely to fall below the 6000 step/day threshold, suggesting functional limitation. People who are predisposed to OA or have confirmed OA should not be discouraged from walking and can benefit from AA 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Poor sleep quality included “fairly poor” or “very bad” while good sleep included “fairly good” and “very good”. Overall comorbidity was assessed using the modified Charlson comorbidity index . The modified WOMAC pain subscale which ranged from 0 to 20 was used in reporting knee pain in “the past 30 days” .…”
Section: Methodsmentioning
confidence: 99%
“…Depression and pain commonly occur together 93 due to a mutually reinforcing relationship. People with OA and concomitant depression symptoms are less active (decline in steps/day) 94 , respond less to systematic depression treatment and have worse pain and depression outcomes 95 .…”
Section: Depression and Mental Healthmentioning
confidence: 99%